Dynamic characteristics of inclined cable - Oh, Jongseok (University of Ottawa (Canada), 2004)
This thesis aims to investigate dynamic characteristics, especially the natural in-plane vibrations, of a perfectly flexible elastic suspended cable. A finite element procedure using the linear elastic rod as cable elements is formulated and a program implemented in Matlab is developed to determine natural frequencies and mode shapes. Results show how the properties of inclined cables meaningfully differ from those of horizontal cables. Influence of cable inclination induces the mixture of mode shapes through the transition range and the region of non-contact crossings of frequency. These phenomena assure that the existence of crossover points is only exception for the case of horizontal cables.
Keywords: Engineering, Civil.